The Effects of Capsella bursa pastoris Capsules on the Severity of Primary Dysmenorrhea: A Randomized Clinical Trial - Saeedeh Ahmadipoor; Fatemeh Nahidi; Faraz Mojab; Malihe Nasiri; Marzieh Kaboudi (Mashhad University of Medical Sciences, 2023)
Introduction: According to the high prevalence of primary dysmenorrhea and its consequences on the quality of life and the effects of nonsteroidal anti- inflammatory drugs consumption, the present study was performed with aim to investigate the effect of the capsella bursa-pastoris on the severity of primary dysmenorrhea. Methods: This triple-blind clinical trial study was conducted in 2022 on 80 girls referred to the comprehensive health service centers of Kermanshah University of Medical Sciences with a history of primary dysmenorrhea. The participants were divided into two groups of 40 people, intervention and control. The intervention group received capsules containing 400 mg of hydroalcoholic extract of the "Capsella bursa pastoris" plant and the control group received 250 mg capsules of mefenamic acid every 8 hours for 3 days for 2 consecutive periods. The research tools were demographic profile questionnaire, menstrual status and physical activity questionnaire, and visual analog scale. Data were analyzed by SPSS software (version 19) and independent t-tests, chi-square, Bonferroni and analysis of variance with repeated measures. P<0.05 was considered statistically significant. Results: Before the intervention, the two groups were similar in terms of pain intensity (p=0.689). The two-factor variance test showed that the two groups had a significant difference in terms of pain intensity after the intervention (p=0.001), but the reduction of pain was more in the capsella bursa-pastoris group. Conclusion: The Capsella bursa-pastoris plant can reduce the severity of primary dysmenorrhoea; Therefore, it is recommended to conduct more researches to confirm the effectiveness and safety of the Capsella bursa pastoris plant.